2021
DOI: 10.3390/jcm10092009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy, Visual Performance and Patient Reported Outcomes with a Trifocal Intraocular Lens: A Six-Year Follow-up

Abstract: (1) Background: To evaluate the efficacy at 6 years postoperative after the implantation of a trifocal intraocular lens (IOL) AT Lisa Tri 839MP. The secondary objective was to evaluate the contrast sensitivity defocus curve (CSDC), light distortion analysis (LDA), and patient reported outcomes (PROs). (2) Methods: Sixty-two subjects participated in phone call interviews to collect data regarding a visual function questionnaire (VF-14), a patient reported spectacle independence questionnaire (PRSIQ), and questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…In the present study, only 1 subject reported seldom needing spectacles for intermediate distances, while for near vision, 88% (22) achieved spectacle independence, and the remaining 12% (3) reported a need for spectacles rarely (1 patient), sometimes (1 patient), and all of the time (1 patient). In the present study, 100% of subjects reported being satisfied or very satisfied with their vision at all distances (PRSIQ, question 2 D), the same as reported by Vargas et al [ 21 ] (100%), and higher than reported by Fernandez et al [ 19 ] and Liu et al [ 22 ] (more than 90%), and Mendicute et al [ 23 ] (more than 80%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, only 1 subject reported seldom needing spectacles for intermediate distances, while for near vision, 88% (22) achieved spectacle independence, and the remaining 12% (3) reported a need for spectacles rarely (1 patient), sometimes (1 patient), and all of the time (1 patient). In the present study, 100% of subjects reported being satisfied or very satisfied with their vision at all distances (PRSIQ, question 2 D), the same as reported by Vargas et al [ 21 ] (100%), and higher than reported by Fernandez et al [ 19 ] and Liu et al [ 22 ] (more than 90%), and Mendicute et al [ 23 ] (more than 80%).…”
Section: Discussionsupporting
confidence: 87%
“…Patient-reported spectacle independence was assessed using a non-validated Spanish translation of the English validated PRSIQ [ 12 ]. In a study assessing patient-reported spectacle independence 6 years after implantation of a trifocal IOL, Fernandez et al [ 19 ] used the same questionnaire and reported the total spectacle independence for far and intermediate distance vision, but 19.4% of subjects reported a need for spectacle use for near vision, 6.5% reported this aid was sometimes needed, and 12.9% rarely needed it. Song et al [ 20 ] reported good visual outcomes by combining a trifocal and an EDOF IOL using the Visual Function Questionnaire (VFQ-25).…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort 84% of patients received Nd: YAG capsulotomy due to PCO. A mean time to capsulotomy of 44 months has been reported in the literature [28]. Additionally, rates of capsulotomy in other studies (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Fernández et al [28] reported disturbing optical phenomena in 32% of the cases, McNeely et al [26] in more than 40% and Brito et al [27] even in 50% of the cases. Although the literature reports the occurrence of optical phenomena with monofocal lenses [30], they do not occur that often.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation